Clinical Utility Findings of a Transcriptomic Psoriasis Biologic Test Demonstrate Altered Physician Prescribing Behavior and Improved Patient Outcomes - Bruce E. Strober; Michael Bukhalo; April W. Armstrong; David Pariser; Leon Kircik; Brian Johnson; Paul Montgomery; Tobin J. Dickerson (Dermatology and Therapy)
Abstract Introduction This randomized, prospective study (MATCH) was designed to assess the clinical utility of a machine learning-based tool (Mind.Px) that predicts patient response to the biologic drug classes used in the management of psoriasis. Methods Patients with psoriasis who were biologic naïve or approaching a medication change owing to nonresponse were enrolled into the study (N = 210). At baseline, a dermal biomarker patch was applied to lesional skin, and Mind.Px test results were provided to physicians for patients in the informed arm of the study prior to biologic selection. The choice of biologic was recorded, and, in the case of physician nonconcordance with Mind.Px test results, a questionnaire was completed to determine the reason for nonconcordance. Patients were evaluated at weeks 4 and 12 after baseline using Psoriasis Area and Severity Index (PASI). Statistical analysis between groups was performed using Fisher’s exact test. Results Physician prescribing behavior was measured with and without the inclusion of Mind.Px test results in the decision-making process (N = 205). Additional comparisons were made to a previously collected data set identical to the Mind.Px-uninformed arm (N = 429). Statistical analysis of concordance between the Mind.Px-informed and Mind.Px-uninformed groups (92.3% versus 62.9%, respectively) showed that when given access to Mind.Px results, physician behavior was significantly altered (p = 8.08 × 10–7). Furthermore, analysis of patients whose physicians followed Mind.Px results showed that not only did more patients reach the clinical endpoint (PASI75) at 12 weeks (p = 5.4 × 10–4), but also more patients reached this endpoint by week 4 than those in the treatment-as-usual arm (p = 0.01). Conclusions These results provide evidence of the clinical utility of Mind.Px by showing that physicians utilize test results in psoriasis biologic decision-making, leading to improved patient outcomes. These improved patient outcomes can also potentially translate into cost savings for healthcare systems. Mind.Px can minimize the trial-and-error approach to psoriasis treatment, and provide physicians, patients, and payers with an effective tool for re-envisioning the management of patients with psoriasis. Clinicaltrials.gov listing NCT05036889.